Menumbuhkan Minat Sains Sejak Dini: Kegiatan Pengenalan IPA di SDN 1 Tumbang Rungan: Cultivating Interest in Science from an Early Age: Science Introduction Activities at SDN 1 Tumbang Rungan - Suhartono, Suhartono; Sundari, Resti; Vari, Yonatan; Fauzi, Toni Dwi; Hartanto, Theo Jhoni; Dinata, Pri Ariadi Cahya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Introducing science to elementary school students in a fun way is a strategic step in establishing a foundation for scientific thinking from an early age. However, the reality in the field shows that the science learning approach is still conventional and less interactive. The limited use of experiments or engaging exploratory activities contributes to a lack of interest and enthusiasm for science among elementary school students. This diminished interest ultimately leads to a poor understanding of scientific concepts. To tackle this challenge, this community service initiative is centered around the theme "Fun and Enjoyable Science Educational Activities for Elementary School Students to Foster Early Interest in Science." This activity is designed with an educational approach that incorporates games and simple experiments relevant to students' daily lives. This community service project is divided into three stages: preparation, which involves collaborating with the school, developing tools and practicum modules, and assigning tasks; execution, where science concepts are introduced to students; and assessment, which focuses on measuring both teacher and student interest in the activities. The exercise successfully cultivated students' interest and excitement for science, as indicated by the responses from both teachers and students in the questionnaires. Every student demonstrated a high level of curiosity and active participation, expressing a desire to repeat the experiment at home. Teachers provided positive feedback, expressing that the practicum module was easy to understand, relevant to the learning material, and could be implemented with simple tools and materials available around the school.